"Spiritus deorum sanctorum" (Dn 4−5) - Tronina, Antoni (The Biblical Annals, 2017)
The Aramaic expression ”rûah.’ĕlāhîn qaddîszîn” is commonly translated, following Heronymus’ Vulgate as „spirit of holy gods”. It has also a more profound sense, as pointed by the context of Dn 4, 5. It says that a prophet takes a particular part in the gifts of God and knows the hidden sense of events. Such an understanding of the „holy spirit” prepares for the reception of the whole of revelation in the Books of the New Testament.